Understanding virtual reality : interface, application, and design - Sherman, William R., (Morgan Kaufmann series in computer graphics., 2019)
Addresses the fundamentals of the medium of virtual reality. VR depends on the human perceptual system and thus this books addresses both the physical and psychological components of the human and how this knowledge can be used to create compelling VR experiences. This book examines the key technological components (hardware and software) for user tracking and other inputs plus visual, aural, haptic, olfactory, and gustatory displays, as wells interaction and navigation interfaces for manipulating, moving, and more--back cover.